Cytonuclear Evolution of Rubisco in Four Allopolyploid Lineages - Gong, Lei; Olson, Mischa; Wendel, Jonathan F. (Molecular biology and evolution, 2014)
Allopolyploidization in plants entails the merger of two divergent nuclear genomes, typically with only one set (usually maternal) of parental plastidial and mitochondrial genomes and with an altered cytonuclear stoichiometry. Thus, we might expect cytonuclear coevolution to be an important dimension of allopolyploid evolution. Here, we investigate cytonuclear coordination for the key chloroplast protein rubisco (ribulose 1,5-bisphosphate carboxylase/oxygenase), which is composed of nuclear-encoded, small subunits (SSUs) and plastid-encoded, large subunits. By studying gene composition and diversity as well as gene expression in four model allopolyploid lineages, Arabidopsis, Arachis, Brassica, and Nicotiana, we demonstrate that paralogous nuclear-encoded rbcS genes within diploids are subject to homogenization via gene conversion and that such concerted evolution via gene conversion characterizes duplicated genes (homoeologs) at the polyploid level. Many gene conversions in the polyploids are intergenomic with respect to the diploid progenitor genomes, occur in functional domains of the homoeologous SSUs, and are directionally biased, such that the maternal amino acid states are favored. This consistent preferential maternal-to-paternal gene conversion is mirrored at the transcriptional level, with a uniform transcriptional bias of the maternal-like rbcS homoeologs. These data, repeated among multiple diverse angiosperm genera for an important photosynthetic enzyme, suggest that cytonuclear coevolution may be mediated by intergenomic gene conversion and altered transcription of duplicated, now homoeologous nuclear genes.